BIAYA-BIAYA DAN PENDANAAN PENDIDIKAN: KECENDERUNGAN DAN DAMPAK KEBIJAKAN - Ade Rukmana; Amirullah; Izudin Hasan; Aprilliantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the dynamics of educational costs and funding, focusing on trends and policy impacts over the past five years at both global and national levels. Using a descriptive qualitative approach and literature analysis, the research identifies three major findings. First, the global and national education sectors face increasing financial pressure due to rising educational costs and fiscal instability, particularly in the aftermath of the COVID-19 pandemic. Second, households experience a growing financial burden as direct and indirect education expenses continue to rise, contributing to widening disparities in access and learning opportunities. Third, although government budget allocations such as Indonesia’s 20% education mandate provide an important foundation for education financing, challenges remain regarding equitable and effective distribution, particularly due to regional fiscal disparities and variations in school management capacity. The study concludes that improving the quality and equity of education requires not only adequate funding but also strengthened governance, targeted budgeting, and sustainable financing strategies to ensure that all learners receive quality educational services.